Perlindungan Hukum Pemilik Sertifikat Elektronik Akibat Kesalahan Penginputan Database yang Dilakukan Oleh Pejabat Berwenang - Agustin Widjiastuti; Kevin Richard Manoppo; Paula Paula (CV Rewang Rencang, 2025)
This study discusses the issue of legal protection for electronic certificate owners due to database input errors made by authorized officials. The objectives of this study are: 1) to determine the legal protection for electronic certificate owners and 2) to determine the party responsible when an error occurs in inputting electronic certificate data. The formulation of the problems raised in this study are: 1) how is the legal protection of electronic certificate owners due to errors in database input, and 2) how is the responsibility of authorized officials when errors occur in electronic certificate data input? This study uses a normative legal method that uses literature studies. The results of this study are: 1) This study discusses legal protection for electronic certificate owners due to database input errors categorized as maladministration according to Article 1 Number 3 of Law No. 37 of 2008. The solution includes strengthening regulations, implementing SOPs based on the principles of legal certainty and accuracy, and public education. Legal efforts include administrative corrections, complaints to the ombudsman, administrative objections, and civil lawsuits, with the principles of legal certainty and accuracy as the main principles, and 2) Errors in inputting the electronic land certificate database by authorized officials can cause material and immaterial losses to certificate owners. The responsibilities include administrative corrections, Ombudsman recommendations, administrative sanctions, and material compensation in accordance with Article 1365 of the Civil Code. Recovery is carried out through objections, administrative appeals, or civil lawsuits to protect rights and legal certainty.